Хаотическое маскирование информационных сигналов с использованием генератора на базе системы Лю - Ivanyuk, P. V.; Politansky, L. F.; Politansky, R. L.; Eliiashiv, О. М. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
Lyapunov exponent spectrum for a chaotic Liu system was calculated in this work. The possibility to set the synchronization between generators based on the system under investigation was shown. A communication system was experimentally realized using chaotic generators.